The Roles of the UK in the Climate Change Regime within Pre- and Post- Brexit Period - Pradnya Nareswari, Ni Luh Putu Paramitha; Parameswari, A.A. Ayu Intan; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 1 (2024): JURNAL DIKSHI, 2024)
This study examines the UK's roles in the climate regime during the pre- and post- Brexit era within the 2008-2021 temporal locus. This writing investigates the UK’s commitments implementation by adopting a leadership framework and scrutinizing its role in climate change as (i) an exemplary leader, (ii) funding, and (iii) a pusher. Referring to secondary data, it reveals that the UK is aiming for the global climate leader title post-Brexit, which exemplifies the role-learning process. This study concludes that the UK shifted its auxiliary role of climate leader to a more central position in its role set, reinforcing its master roles of responsible great power and leader of the global climate regime. The UK provides several modes of leadership to show its commitment towards climate regime, namely (a) unilateral leadership by establishing good examples of climate policy, (b) assisting other climate-vulnerable countries on the accessibility of climate funds by acting as a structural leader, and (c) giving the image as a robust actor with a timely response to climate issues by its pusher roles adapted from problem-solving leadership. Keywords : Brexit, climate leadership, roles implementation, national interest, the United Kingdom